Over half of fraud incidents in England and Wales are now cyber-related. Issue 11 (November 2017) - Unknown
Abstract : The latest figures from the UK's Office of National Statistics (ONS) would seem to show a slight overall drop in cybercrime. However, fraud figures are up and it may be too soon to celebrate as the statistics remain 'experimental'.